2011
DOI: 10.1186/1743-7075-8-9
|View full text |Cite
|
Sign up to set email alerts
|

Iron bioavailability from a tropical leafy vegetable in anaemic mice

Abstract: Telfairia occidentalis is a vegetable food crop that is indigenous to West Africa. The leaves and seeds are the edible parts of the plant and are used in everyday meals by incorporation into soups and stews. Previous studies have attributed improved haematological indices to the vegetable and have advocated the use of T. occidentalis in the treatment of anemia. This study investigates the ameliorative effects of T. occidentalis when compared to FeSO4 as a reference salt in anaemic mice. It also compares the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…This observation may have been responsible for the marked increase in PCV of rats administered with the extract as seen in Table 2. This is consistent with reports that iron is needed for the formation of haemoglobin, 14 which aid the formation of RBCs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation may have been responsible for the marked increase in PCV of rats administered with the extract as seen in Table 2. This is consistent with reports that iron is needed for the formation of haemoglobin, 14 which aid the formation of RBCs.…”
Section: Discussionsupporting
confidence: 93%
“…Telfairia occidentalis is cultivated in west Africa 12,13 and commonly known as fluted pumpkin or Ugwu in Nigeria. 14 Several studies [15][16][17][18][19][20][21][22][23][24][25] have been carried out on the therapeutic potentials of T. occidentalis. One study 26 reported the effect of diet formulations of the air-dried leaves of T. occidentalis on haematological parameters in rats.…”
Section: Introductionmentioning
confidence: 99%
“…In an experiment involving 2-week supplementation in rats, no significant difference was seen in several hemoglobin parameters (hemoglobin concentration, mean corpuscular volume, mean corpuscular hemoglobin, and mean corpuscular hemoglobin concentration) between soybean sprouts enriched in ferritin (by germination in a FeSO4 solution), ferritin isolate, control ferrous sulfate and a control group of healthy animals [ 86 ]. A nonsignificant difference in hematologic indices was reported in an in vivo , parallel group experiment comparing a leaf extract of Telfairia occidentalis, ferrous sulfate and a control group fed on an iron-deficient diet with no treatment [ 87 ] (careful examination of the data, however, suggest that this was mainly the results of insufficient statistical power, the effect of the extract being about half of that seen with the inorganic salt). Nevertheless, this experiment does show that increase of the extract dosage allows for acceptable levels of Hb and that iron administered from herbal sources may be sufficiently bioavailable).…”
Section: Discussionmentioning
confidence: 99%
“…This study also agreed with the work of Salman et al (2008), who reported that there was a significant increase in the hematological parameters of rats that were treated for two weeks with the aqueous leaf extract of fluted pumpkin. Some scientists have proposed the use of fluted pumpkin in treatment of anemia, following studies which reported that extracts of fluted pumpkin helps to maintain blood level in subjects given its extracts (Fiona and Latunde -Dada, 2011). …”
Section: Discussionmentioning
confidence: 99%